Uji Ketahanan dan Ekspresi Gen pada Event Tebu Produk Rekayasa Genetika Tahan Hama Penggerek Batang - Hawari Bai'atur Ridwan (Fakultas Pertanian, 2026)
Sugarcane (Saccharum officinarum L.) has a high sucrose content and is processed into sugar as the main product. The supply of sugar in crystal form fluctuated in 2022-2024 due to the susceptibility of sugarcane plants, especially the Bululawang variety, to stem borers (Chilo sacchariphagus). This susceptibility led to the development of genetically modified (GM) crops by inserting the Crystal (Cry) gene from the bacterium Bacillus thuringiensis (Bt). GM crops were developed in the Bululawang variety of sugarcane by combining the Cry1Ab and Cry1Ac genes, which produced several GM sugarcane events. The Cry1Ab-Cry1Ac fusion gene GM sugarcane events were then evaluated through resistance testing against C. sacchariphagus to determine the level of resistance of these events. High intensity attacks by C. sacchariphagus can increase the production of reactive oxygen species, which cause oxidative stress and lead to cell damage. Cell damage can be minimized through the activation of antioxidant enzyme genes, such as SOD, APX, CAT, and POD. This study aims to determine the effect of C. sacchariphagus attacks on the resistance of GM sugarcane events and the expression value of antioxidant enzyme genes. The method used in this study was a single-factor completely randomized design consisting of seven experiments, namely one Bululawang variety and six genetically modified sugarcane events from the BRIN collection. The results showed that the seven experiments did not produce significant differences in mortality, but did produce significant differences in the incidence of dead heart and the length of borer tunnels, as well as very significant differences in the number of new tillers. The expression of antioxidant enzymes (CAT, SOD, and APX) showed downregulation; however, there were differences in fold change values across experiments, reflecting variations in the defensive response of PRG sugarcane to attacks by C. sacchariphagus.
FINALISASI oleh Arif 2026 Juni 04
Keywords: productivity; larvae; toxicity; resistance; gene expression level